(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to test Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), Share Prices at Conventional Banks listed on the Indonesia Stock Exchange. This type of research is explanatory. The study population is a Conventional Bank listed on the Indonesia Stock Exchange period 2014-2016 which amounted to 43 banks and sampling as many as 26 banks using techniques p urposive sampling , which is determined based on criteria. Mechanical analysis were used is the analysis of regression linear multiple significance level of 5%, in the process with Software Eviews 8.0. The results showed that ROA had no effect on stock prices, while NPM and EPS had a partial effect on stock prices. ROA, NPM and EPS have a simultaneous effect on stock prices.